Ensuring the Protection of Women’s Rights in Armed Conflicts - Roza Omer Hamadamin; Muheadin Hassan Yousif (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Throughout history, women have often been subjected to various forms of victimization during armed conflicts, being among the most marginalized segments of society. Regardless of age, race, ethnicity, or nationality, women have consistently suffered in both international and non-international armed conflicts (IAC and NIAC). In response to these realities, humanitarian laws have been established to safeguard civilians generally, with specific provisions aimed at protecting women during armed conflicts (ACs). Despite the existence of international regulations and measures, there remains a lack of robust assurances for the protection of women in such contexts. This study aims to illuminate the issue of women’s protection during ACs by examining pertinent international standards within the framework of international law